Voice and Agency : Empowering Women and Girls for Shared Prosperity - Klugman, Jeni; Hanmer, Lucia; Twigg, Sarah; Hasan, Tazeen; McCleary-Sills, Jennifer; Santamaria, Julieth (Washington, DC: World Bank Group, 2014)
The 2012 World Development Report recognized that expanding women's agency - their ability to make decisions and take advantage of opportunities is key to improving their lives as well as the world. This report represents a major advance in global knowledge on this critical front. The vast data and thousands of surveys distilled in this report cast important light on the nature of constraints women and girls continue to face globally. This report identifies promising opportunities and entry points for lasting transformation, such as interventions that reach across sectors and include life-skills training, sexual and reproductive health education, conditional cash transfers, and mentoring. It finds that addressing what the World Health Organization has identified as an epidemic of violence against women means sharply scaling up engagement with men and boys. The report also underlines the vital role information and communication technologies can play in amplifying women's voices, expanding their economic and learning opportunities, and broadening their views and aspirations. The World Bank Group's twin goals of ending extreme poverty and boosting shared prosperity demand no less than the full and equal participation of women and men, girls and boys, around the world.